Construcción barrial del Instituto de Crédito Territorial. Configuración social y espacial de la Comuna de Robledo de Medellín, a través de la vivienda social (1959-1973) (2014)
ABSTRACT: The paper presents the methodology of social housing construction of the Territorial Credit Institute (ICT) and the participation of other stakeholders, especially the awardees. The ICT was the main entity that contributed to the socio-spatial configuration of the Robledo Commune in Medellin during the period 1959-1973. This program was subject to international design policies, methodology and allocation that were unaware to the conditions of the locals and their context. The results of this effort were limited, and the development of Robledo, one of the largest Communes in the city, was slow, fragile and complicated. In this paper, we review studies about state housing construction targeting poor people in Latin America, Colombia, and Medellin. Likewise, the revision of both official and unofficial manuscripts, as well as the use of oral history, allowed us to observe some difficulties in this process that were finally settled by the inhabitants. From this experience, structural changes were made in official housing plans.